International Network for Exchanging Experience on Statistical Handling of Granular Data (INEXDA). - Hirsch, Christian (International Journal of Population Data Science, 2018)
The financial crisis of 2007/08 has highlighted the need for using granular data on financial institutions and markets to detect risks and imbalances in the financial sector. Administrative data producers are witnessing a growing need to improve granular data access and sharing. When sharing granular data, data producers face significant legal and technical challenges related to, among others, safeguarding statistical confidentiality. To meet the demand of data users and data compilers for (granular) data sharing, the International Network for Exchanging Experience on Statistical Handling of Granular Data (INEXDA) was established on 6 January 2017. Current INEXDA members are the Banco de España, Banca d'Italia, the Banco de Portugal, the Bank of England, the Banque de France, the Deutsche Bundesbank, and the European Central Bank. INEXDA provides a platform for administrative data producers to exchange practical experiences on the accessibility of granular data, on metadata as well as on techniques for statistical analysis and data protection. During the INEXDA meeting in Paris, Julia Lane has presented the Administrative Data Research Facility (ADRF). Following her presentation several INEXDA members expressed interest in obtaining more information about the approach taken by ADRF. This presentation describes the interaction between INEXDA and ADRF. The views expressed here are those of the author and do not necessarily reflect those of the Deutsche Bundesbank, ADRF, or the INEXDA Network.